Shazam! : the new beginning 30th anniversary deluxe edition - Thomas, Roy, 1940-; Thomas, Dann (DC Comics, 2017)
"He was one of the greatest heroes of comics' Golden Age--a square-jawed colossus with a child's optimistic spirit. Then a great crisis came that destroyed his world and erased his adventures from history. But even during the grim and gritty era that followed, this force of pure goodness continued to shine through the gloom like the bolt of lightning that strikes whenever young Billy Batson says the magic word... SHAZAM! Then, in 1987, the celebrated saga of the orphaned boy with godlike powers began anew. Under an all-new creative team, DC's Captain Marvel was reimagined as a 15-year-old teenager--one who is fated to grow up much faster than he'd hoped. Arrayed against him are some of the most menacing villains the world has ever seen: Dr. Sivana, a scientific genius as evil as he is intelligent; Captain Nazi, an Aryan übermensch bent on building a new American reich; and Black Adam, a 5,000-year-old tyrant with the same powers as Captain Marvel and the cold-hearted ambition to rule the world! SHAZAM!: THE NEW BEGINNING 30TH ANNIVERSARY DELUXE EDITION presents the complete Shazam! stories from legendary comics author Roy Thomas, his co-writer and wife Dann Thomas and acclaimed artists Tom Mandrake, Rick Stasi and Rick Magyar."--